Cysteine-based protein folding modulators for trapping intermediates and misfolded forms. Issue 41 (21st September 2022) - Nishino, Hayato; Kitamura, Mai; Okada, Shunsuke; Miyake, Ryosuke; Okumura, Masaki; Muraoka, Takahiro
Abstract : In this study, cysteine-containing dipeptides conjugated with amino acids possessing mono- and diamino-groups were developed as protein-folding modulators affording non-native forms through intermolecular disulfide-bond formation. Abstract : Folding is a key process to form functional conformations of proteins. Folding via on-pathway intermediates leads to the formation of native structures, while folding through off-pathways affords non-native and disease-causing forms. Trapping folding intermediates and misfolded forms is important for investigating folding mechanisms and disease-related biological properties of the misfolded proteins. We developed cysteine-containing dipeptides conjugated with amino acids possessing mono- and diamino-groups. In oxidative protein folding involving disulfide-bond formation, the addition of cysteine and oxidized glutathione readily promoted the folding to afford native forms. In contrast, despite the acceleration of disulfide-bond formation, non-native isomers formed in significantly increased yields upon the addition of the dipeptides. This study provides a molecular design of cysteine-based protein-folding modulators that afford proteins adopting non-native conformations through intermolecular disulfide-bond formation. Because of the intrinsic reversibility of the disulfide bonds upon redox reactions, the disulfide bond-based approach demonstrated here is expected to lead to the development of reversible methodologies for trapping transient and misfolded forms by intermolecular disulfide bond formation and restarting the folding processes of the trapped forms by subsequent cleavage of the intermolecular disulfide bonds.